The Oxford handbook of Islamic law - Emon, Anver M. ca. 20./21. Jh.; Ahmed, Rumee ca. 20./21. Jh. (Oxford Oxford University Press USA - OSO, 2019)
A comprehensive guide to Islamic legal scholarship, this Handbook offers a direct and accessible introduction to Islamic law and the academic debates within the field. Topics include textual sources and authority, institutions, substantive legal areas, Islamic legal philosophy, and Islamic law in the Muslim World and in Muslim minority countries.
Cover -- The Oxford Handbook of Islamic Law -- Copyright -- Contents -- Editors' Introduction -- Notes on the Contributors -- Part I Discipline and Critique -- A. Islamic Legal Studies: Discipline and Critique -- 1 Islamic Legal Studies: A Critical Historiography -- 2 Fiqh -- 3 Islamic Law and Gender -- B. Islamic Legal Studies: Disciplinary Approaches -- 4 Islamic Law and Theology -- 5 Anthropology and Islamic Law -- 6 Falsafa and Law -- Part II Legal Theory and Institutions -- A. Legal Theory -- 7 Ijtihad -- 8 Imami Shi'i Legal Theory: From its Origins to the Early Twentieth Century -- 9 Custom in the Islamic Legal Tradition -- 10 The Historiography of Sunni Usul al-​Fiqh -- 11 Ijma' -- B. Institutions -- 12 Qadi -- 13 Hisba and Muhtasib -- 14 The Mazalim in Historiography -- Part III Origins, Empires, and States -- A. Historical Studies -- 15 Origins of and Influences on Islamic -- 16 The Classical Period: Scripture, Origins, and Early Development -- 17 The Age of Development and Continuity, 12th-​15th Centuries CE -- 18 The Historiography of Islamic Law During the Mamluk Sultanate -- 19 Law in the Ottoman Empire -- 20 A Historiography of Islamic Law in the Mughal Empire -- 21 Delivering Justice: The Monarch's 'Urfi Courts and the Shari'a in Safavid Iran -- 22 Anglo-​Muhammadan Law -- 23 Legislation as an Instrument of Islamic Law -- Part IV Regional Variations -- A. Muslim-​Majority States -- 24 Islamic Law and Society in Southeast Asia -- 25 Islamic Law in Post-​Revolutionary Iran -- 26 The Turkish Republic -- 27 Islamic Law in South Asia: A Testament to Diversity -- B. Muslim Minorities -- 28 The Incorporation of Shari'a in North America: Enforcing the Mahr to Combat Women's Poverty Post-​Relationship Dissolution -- 29 Islamic Law in Western Europe -- 30 Shari'a in Australia -- Part V Substantive Legal Areas -- A. Case Studies.
Description based on publisher supplied metadata and other sources
Keywords: Islamic Law; Electronic books; Aufsatzsammlung